Exploring the Potential of Metal–Organic Frameworks for the Separation of Blends of Fluorinated Gases with High Global Warming Potential. Issue 1 (21st October 2022) - Sosa, Julio E.; Malheiro, Carine; Castro, Paulo J.; Ribeiro, Rui P. P. L.; Piñeiro, Manuel M.; Plantier, Frédéric; Mota, José P. B.; Araújo, João M. M.; Pereiro, Ana B.
Abstract: The research on porous materials for the selective capture of fluorinated gases (F‐gases) is key to reduce their emissions. Here, the adsorption of difluoromethane (R‐32), pentafluoroethane (R‐125), and 1, 1, 1, 2‐tetrafluoroethane (R‐134a) is studied in four metal–organic frameworks (MOFs: Cu‐benzene‐1, 3, 5‐tricarboxylate, zeolitic imidazolate framework‐8, MOF‐177, and MIL‐53(Al)) and in one zeolite (ZSM‐5) with the aim to develop technologies for the efficient capture and separation of high global warming potential blends containing these gases. Single‐component sorption equilibria of the pure gases are measured at three temperatures (283.15, 303.15, and 323.15 K) by gravimetry and correlated using the Tóth and Virial adsorption models, and selectivities toward R‐410A and R‐407F are determined by ideal adsorption solution theory. While at lower pressures, R‐125 and R‐134a are preferentially adsorbed in all materials, at higher pressures there is no selectivity, or it is shifted toward the adsorption R‐32. Furthermore, at high pressures, MOF‐177 shows the highest adsorption capacity for the three F‐gases. The results presented here show that the utilization of MOFs, as tailored made materials, is promising for the development of new approaches for the selective capture of F‐gases and for the separation of blends of these gases, which are used in commercial refrigeration. Abstract : Four different metal–organic frameworks (MOFs) and one zeolite are studied for the adsorption of fluorinated gases and are evaluated for the separation of refrigerants with high global warming potential. The utilization of MOFs for these purposes is promising and by selecting materials with different porous characteristics and chemistries, it is possible to fine‐tune the separation of commercial refrigerants.